Service Quality Measurement System with Method Service Quality (SERVQUAL) at BRI Kedungwaru Unit, Tulungagung Regency - Wahyudi, Tri; Forijati, RR; Heriadi, Agustono (Universitas Negeri Surabaya, 2024)
As the growth of customers at BRI increases, BRI management is required to satisfy the service they provide to customers in order to maintain the achievements they have achieved and reduce customer complaints regarding their dissatisfaction with bank services, so it is important for banks to know the service in the eyes of customers in in terms of quality service and customer satisfaction. The research technique in this research is Development Research or Information Technology Engineering and this research uses a quantitative approach where data will be collected by carrying out measurements, which will then produce data figures. Meanwhile, the sampling method used was Purposive Sampling. This research was conducted at the BRI Unit office using a sample of 50 customers. Data was collected by distributing questionnaires. Next, the data will be sampled for testing system development built using the Service Quality Method. The results obtained from this research are software engineering that displays satisfaction criteria assessments that can be used to improve and enhance services in providing services to consumers.